2021
DOI: 10.3390/foods10081927
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Sulforaphane Content in Broccoli Sprouts and Subsequent Sulforaphane Extraction

Abstract: Broccoli sprouts contain 10–100 times higher levels of sulforaphane than mature plants, something that has been well known since 1997. Sulforaphane has a whole range of unique biological properties, and it is especially an inducer of phase 2 detoxication enzymes. Therefore, its use has been intensively studied in the field of health and nutrition. The formation of sulforaphane is controlled by the epithiospecifier protein, a myrosinase co-factor, which is temperature-specific. This paper studies the influence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 19 publications
(22 reference statements)
2
5
1
Order By: Relevance
“…The optimum conditions that maximize SFN content were blanching at 61 • C for 4.8 min. The optimum temperature coincides with Tríska et al [17], who concluded that temperature is the key factor in SFN formation in broccoli sprout processing, and that its optimum should range between 60 and 70 • C. Our values match the best temperature reported by [19] for broccoli sprouts (60 • C) and are close to the optimum reported by Pérez et al [10] for broccoli florets (57 • C for 13 min). Our results also agree with Mahn et al [11], who reported an increase of SFN content in broccoli florets by 2-fold in comparison with its fresh state when an ultrasound-assisted blanching was applied at 60 • C for 4 min.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The optimum conditions that maximize SFN content were blanching at 61 • C for 4.8 min. The optimum temperature coincides with Tríska et al [17], who concluded that temperature is the key factor in SFN formation in broccoli sprout processing, and that its optimum should range between 60 and 70 • C. Our values match the best temperature reported by [19] for broccoli sprouts (60 • C) and are close to the optimum reported by Pérez et al [10] for broccoli florets (57 • C for 13 min). Our results also agree with Mahn et al [11], who reported an increase of SFN content in broccoli florets by 2-fold in comparison with its fresh state when an ultrasound-assisted blanching was applied at 60 • C for 4 min.…”
Section: Discussionsupporting
confidence: 90%
“…In the present work, we achieved a 330% increment compared to fresh sprouts. The exceptionally high values obtained in this work may be related to the treatment but also to the broccoli cultivar and the culture conditions, which differ from that reported elsewhere [17,23].…”
Section: Discussioncontrasting
confidence: 90%
See 3 more Smart Citations